PEMAHAMAN KONSEP TATTWA DENGAN KETRAMPILAN UPAKARA BHUTA YADNYA - Ni Ketut Sudani (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
This study aims at investigating whether the cooperative learning can improve the understanding of the concept of tattwa in the Hindu subjects for students of class VIII A in SMP PGRI Gianyar 4 in Bakbakan and the cooperative learning can improve the creativity of upakara skills in Bhuta Yadnya Hindu subjects class VIII A in SMP PGRI Gianyar 4 in Bakbakan. In accordance with the observation then in the reflection determined that the actions used to work together in groups havebeen able to improve students’ understanding with the concept of tattwa in Upakara Bhuta Yadnya learning material.